2013
DOI: 10.1021/ja311734d
|View full text |Cite
|
Sign up to set email alerts
|

Mallard Blue: A High-Affinity Selective Heparin Sensor That Operates in Highly Competitive Media

Abstract: We report the simple synthesis and full investigation of a novel heparin binding dye, mallard blue, an arginine-functionalized thionine. This dye binds heparin in highly competitive media, including water with high levels of competitive electrolyte, buffered aqueous solution and human serum. The dye reports on heparin levels by a significant change in its UV–vis spectroscopic profile. Molecular dynamics modeling provides detailed insight into the binding mode. Heparin binding is shown to be selective over othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 35 publications
1
57
0
Order By: Relevance
“…For the most part, these interactions are susceptible to disruption at ionic strengths in the physiologic range, and they thus cannot be used for direct heparin assays in serum or plasma; however, the recently described Mallard blue [named after the steam locomotive (Hale, 2005), not the duck], and Heparin Red (Szelke et al, 2010) give improved affinity for heparin and can be used to measure heparin concentrations in serum directly (Bromfield et al, 2013a), in contrast with older methods that require prior chromatographic isolation of heparin (Jaques et al, 1990).…”
Section: A Heparin Interactions With Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the most part, these interactions are susceptible to disruption at ionic strengths in the physiologic range, and they thus cannot be used for direct heparin assays in serum or plasma; however, the recently described Mallard blue [named after the steam locomotive (Hale, 2005), not the duck], and Heparin Red (Szelke et al, 2010) give improved affinity for heparin and can be used to measure heparin concentrations in serum directly (Bromfield et al, 2013a), in contrast with older methods that require prior chromatographic isolation of heparin (Jaques et al, 1990).…”
Section: A Heparin Interactions With Small Moleculesmentioning
confidence: 99%
“…Interaction with small molecule dyes can be used for heparin in aqueous solutions of low ionic strength (Templeton, 1988), but the dyes Mallard blue and Heparin Red, capable of binding heparin quantitatively in serum, were only recently developed (described above; Bromfield et al, 2013a). Earlier methods have Pharmacology of Heparin and Related Drugs relied on prior removal of heparin from the biologic medium using precipitation, cation exchange chromatography (Jaques et al, 1990), or immobilized polylysine (Mohammad et al, 1980).…”
Section: Physicochemical Quantificationmentioning
confidence: 99%
“…In recent years, several nanocomposites or their redox products have been gradually used to design and build a novel biosensing interface because of their good electrochemical activity and strong adsorption ability. [32][33][34][35][36] In the development of new biosensing interface, label-free style electrochemical sensor, with the introduction of special redox mediator for specific target biomarkers, is attractive. The electron mediator thionine can be used to construct label-free electrochemical immunosensors because of its favorable electron transfer capability; however the stability of the electrode remains to be improved.…”
mentioning
confidence: 99%
“…NOE measurements on free 9 suggested that, as for 7 , terminal side-chain groups are able to penetrate the cavity (see Figure S40). The affinity for glucosammonium was lowered by competing ions, as expected for electrostatic interactions,[13] but K a  values remained quite high even at physiological salt levels (154 m m NaCl). Galactosammonium 14 ⋅H + was bound 3–13 times less strongly than glucosammmonium, thus showing that the all-equatorial preference of the cavity is maintained.…”
mentioning
confidence: 99%